Reporting of oral chemical restraint in the Mental Health Services Monthly Statistics for England - Thomas Cranshaw; Harry Matchette-Downes; Keith Reid (BJPsych Bulletin)
Aims and method This study examines more than 5.8 million bed days of data from private and National Health Service care providers who contribute to the Mental Health Services Monthly Statistics in the UK. The use of oral chemical restraint is compared with provider size, and the relative use of oral chemical restraint as opposed to seclusion is investigated.